"The types of kids we get are different"—The distinguishing characteristics of school choosers in Detroit, Michigan. Issue 1 (2nd January 2018) - Hamlin, Daniel
ABSTRACT: Providing improved educational options for low-income African American families has been one of the primary objectives of the charter school movement. However, among demographically similar families, school choosers may possess subtle advantages compared to nonchoosers, leading to biased estimates of charter school performance in nonexperimental research. This study examines within-group differences between school choosers and nonchoosers in Detroit, Michigan through semistructured interviews with parents ( n  = 31) and teachers ( n  = 23) in charter and public schools. Findings indicate differences between school choosers and nonchoosers in access to transportation, experience, social and professional networks, orientation toward choice, parental involvement, and home stability. These differences offer insight into potential controls for self-selection bias that may lead to improved statistical evaluations using nonexperimental methods.